Genetics of hereditary motor and sensory neuropathy and the Costa Rican contribution - Leal, Alejandro (Revista de Biología Tropical, 2004)
Hereditary motor and sensory neuropathy (HMSN) or Charcot-Marie-Tooth disease (CMT) is the most common hereditary illness of the peripheral nervous system. The genetics and the physiopathological aspects of the disease clarified until know, are here summarized. More than twenty genes and ten additional loci have been related with HMSN. These findings contribute to understand the metabolism of peripheral nerves and give the basis for molecular diagnostics and future therapy. Several Costa Rican families with CMT have been identified, specially with axonal forms. Two families present mutations in the myelin protein zero gene (MPZ). In addition, linkage have been found between the disease and locus 19q13.3 in an extended family, and a mutation segregating with the disease is present in a candidate gene of the critical interval. Costa Rica has several advantages for genetical studies, that can contribute importantly in the generation of knowledge in the neurogenetical field.